Identifikasi Persepsi Wisatawan Terhadap Daya Tarik Wisata Gastronomi Lokal Di Floating Market Lembang - Marsha, Agni; Turgarini, Dewi; Putri, Dias Pratami (HeadWay Research & Developemnt, 2024)
Floating Market Lembang is a famous local gastronomic tourism destination in West Bandung Regency, offering a variety of local foods. Pre-study results indicate that tourists are interested in purchasing local foods but are more interested in purchasing contemporary foods. This study provides deeper insight into how tourists perceive local gastronomy. The purpose of this study was to determine tourists' perceptions of the local gastronomic tourism attractions at Floating Market Lembang. The research design used in this study was a mixed method approach (qualitative and quantitative) with a Concurrent Triangulation Strategy approach through data collection through interviews, observations, and questionnaires. Interviews were conducted with Nona Helix stakeholders and questionnaires were distributed to 100 tourists who had visited Floating Market Lembang. The results of this study indicate that tourists' perceptions of the tourist attractions of Floating Market Lembang, in terms of tourist attraction components, obtained very good results with an average percentage score of 88.20%. This proves that the local gastronomic tourism object at Floating Market Lembang has a well-available tourist attraction component.